(3cGed GdJhGQjNs - (3GdTjHGfqj GdLRQj, CHh GdMSf (B, (3GHf GdCKjQ, YR GdOjf, Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO, J (B630 (3g`s
(3ChdgG (B:s
(3PcQ GdhbJ GdPj GHJOF ajg HYed GdJGQjN aj GdESdGe ; bjd(B: (3deG bOe QShd Gddg (B- (3Udi Gddg Ydjg hSde (B- (3Edi GdeOjfI CeQ HYed GdJGQjN hGdUMjM GdeTghQ Cf YeQ Hf GdNWGH CeQ HhVY GdJGQjN s
(3BNQgG (B:s
(3Ke ONdJ SfI SHY hKdGKjf adeG QCi YeQh Cf CeQ Cgd GdYQGb bO GTJO, hNGa GdgdGc, bGd deYGhjI(B: (3gd dc aj CeQ CYQVg Ydjc dG jRjOfG EdG GLJeGYG, hdG jRjOge EdG aQbI? bGd(B: (3fYe bGd(B: (3fQaY GdeUGMa, Ke fbhd deG ajgG(B: (3gPG Mce HjffG hHjfce eG QaYhgG EdG NOjYI hhgfG hs
(3JHUQI GdYfhGf (B:s
(3GdcGed aj GdJGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\331s
(3cTa GdXfhf (B2\1380s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs